(untitled) (The Pretoria Student Law Review, 2021)
It has always been with a bit of introspection and guilt that I have considered this statement by the great statesman. However to what extent is this statement still relevant, given the backdrop against which Kenyatta made these infamous words? Surely, Kenyatta spoke of some sort of intense political battle, waging between coloniser and the rebellious or guerilla political movements of the colonised. Surely this analogy that Kenyatta spoke of decades ago ceases to exist in modern times, as the concretisation of rights has occurred, and no such battle can even exist in modern society. The above conceptions, although ideologically ideal are practically flawed. A new form of battle is waging war. A new form of battle is waging war. As a consequence of the worldwide acceptance of the political philosophies of democracy and democratic governance, ancillary philosophies like the economic philosophy of capitalism have become intrinsic in society. What we have experienced is rather a shift from this fight for democracy between the colonisers and indigenous African people, to a fight for supremacy between those who advocate individual and those who articulate communal interests.